Using remote sensing and geographical information system to establish the landslide sensitivity map for Son La city area - Thach, Nguyen Ngoc; Canh, Pham Xuan (VNU Journal of Science: Earth and Environmental Sciences, 2011)
Abstract. Son La city is a social-economical centre of Son La province. It is located  in the north-west high mountainous area of  Viet Nam, where the majority of people is ethnic minority. This area plays an important role for development of the Son La province in particularly and also for all  the north west mountainous region. During development from a town to a city, recently, Son La has planned for quickly increasing and modernization of its infrastructure such as traffic system, public construction, new building… Those works have seriously interfered to the ancient balance of slope. Beside of natural effecting as earthquarke, slope gravity, rainfall…, constructional process has a strongly impact to break the natural balance, to appear the hidden gravitational hazard and increase landslide hazards. By using remote sensing technique with SPOT image of scale 1:50.000 and ENVI 4.3, ARCGIS 9.1 softwares, the study try to evaluate and estimate the landslide in relations with  different physical elements such as geology, geomorphology, geo-engineering, tectonics, seismology, hydrology,  hydrogeology, etc.  Result of the study presents a sensitivity map for landslide and different scenarios for landslide risk. These products has been used as scientific references for local government in environmental protection planning Keywords: Landslide, parameters, easement, remote sensing and GIS, integration, scenario.